The Khmer Rouge tribunal : powers, politics, and resistance in transitional justice - Bernath, Julie (Madison, Wisconsin : The University of Wisconsin Press, 2023)
"From 1975 to 1979, while Cambodia was ruled by the brutal Communist Party of Kampuchea (Khmer Rouge) regime, torture, starvation, rape, and forced labor contributed to the death of at least a fifth of the country's population. Despite the severity of these abuses, civil war and international interference prevented investigation until 2004, when protracted negotiations between the Cambodian government and the United Nations resulted in the establishment of the Extraordinary Chambers in the Courts of Cambodia (ECCC), or Khmer Rouge tribunal. The resulting trials have been well scrutinized, with many scholars seeking to weigh the results of the tribunal against the extent of the offenses. Here, Bernath instead deliberately decenters the trials in an effort to understand the ECCC in its particular context-and the degree to which notions of transitional justice generally must be understood in particular social, cultural, and political contexts. She focuses on "sites of resistance" to the ECCC, including not only members of the elite political class but also citizens who do not, for a variety of tangled reasons, participate in the tribunal-and even resistance from victims of the regime and participants in the trials. Bernath demonstrates that the ECCC both shapes and is shaped by long-term contestation over Cambodia's social, economic, and political transformations, and thereby argues that transitional justice must be understood locally rather than as a homogenous good that can be implanted by international actors"--
Includes bibliographical references and index.
Keywords: Extraordinary Chambers in the Courts of Cambodia; Transitional justice -- Cambodia; Trials (Crimes against humanity) -- Cambodia; Justice, Administration of -- Political aspects -- Cambodia